Silat Durian Tapak dalam Perkembangan Degradasi Budaya di Kelurahan Kuranji Padang (2007-2018) - Silvani Silvani; Siti Fatimah (Jurnal Kronologi, 2020)
This research contains about the development of durian tapak silat which is located in the village of Kuranji as well as targeted efforts in maintaining the culture of pencak silat amid cultural degradation. This research uses the historical method which consists of four stages: first, heuristics or data collection, secondly the source criticism and interpretation of the data, finally making history writing so that this writing can be completed. The results of this study indicate that in the village of kuranji there are non-formal educational institutions engaged in the preservation of values and culture, namely pencak silat. The target of silat durian tapak was established in 1980, but the development ang change began in 2007 since it was inaugurated by the Mayor of Padang under the leardership of Erman Jamal. During the leadership of germany, Jamal began to form an organizational structure and management that were recognized leaglly by adat and government stakeholders. Since its establishment until now the number of enthusiast has increased. The form of durian in maintaining cultural degradation that occurred in Kuranji village is to seek financial assistance for the target so that facilities are equipped, conduct promotions by attending each invitation and making billboards as a form of promotion.